A high thermal conductivity flexible composite insulating paper and its preparation method and application

By using a composite structure of two layers of aramid insulating paper and a layer of corona-treated PI film in the insulation material, and using a thermally conductive adhesive, the problem of low thermal conductivity of the insulation material is solved, and thermal conductivity, insulation and Efficient combination of mechanical properties.

CN118958052BActive Publication Date: 2025-01-17YANTAI TAYHO ADVANCED MATERIALS RES INST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411425896.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-17
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The prior art is difficult to construct thermal conductivity paths in polymer polymer systems, resulting in low thermal conductivity of insulating materials and cannot meet the high requirements of thermal conductivity, insulation and mechanical properties at the same time.

Method used

It uses a composite insulating paper composed of two layers of aramid insulating paper and a layer of corona-treated PI film, and is bonded by a thermally conductive adhesive. The thermally conductive adhesive contains hydroxylated hexagonal boron nitride nanosheets and nanometer Alumina powder.

Benefits of technology

The thermal conductivity of composite insulation paper is significantly improved, and the thermal conductivity can even be increased by 13 times, while maintaining high insulation and mechanical properties, and reducing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118958052B_ABST
    Figure CN118958052B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of insulating composite paper processing, and specifically to a high thermal conductivity flexible composite insulating paper and a preparation method and application thereof, wherein the composite insulating paper comprises at least two layers of aramid insulating paper and a layer of PI film, the aramid insulating paper is pressed on both sides of the PI film respectively, and the PI film and the aramid insulating paper are bonded by a thermally conductive adhesive; the aramid insulating paper contains a thermally conductive filler, and the PI film is a PI film that has been corona treated. The thermally conductive filler is hydroxylated hexagonal boron nitride. The composite insulating paper is applied to the insulation field of electrical equipment. The composite insulating paper of the present invention uniformly embeds the high thermal conductivity filler inside the aramid paper, and by compounding with the thermally conductive adhesive and the thermally conductive PI film, a thermal conductive path is constructed at the interface to solve the problem of difficult interface heat transfer. The composite insulating paper also has excellent thermal conductivity, insulation performance and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-thermal-conductivity flexible composite insulating paper and a preparation method and application thereof, belonging to the technical field of insulating composite paper processing. Background Art

[0002] The soft composite material for electrical insulation is a composite of two or more different insulating materials, which is made of plastic film and / or fiber materials such as impregnated or non-impregnated paper, textiles or non-textiles through adhesives. Compared with the traditional aramid pure paper for electrical insulation, it not only has the high temperature resistance and puncture resistance of aramid paper, but also has the characteristics of high strength, high tear resistance and good insulation performance of the insulation film. The introduction of the insulation film also further reduces the overall cost of the insulation paper.

[0003] High-voltage and high-speed motors for new energy vehicles are becoming more and more popular. Composite insulation materials have great advantages in high-voltage resistance and process adaptability, and have become the mainstream insulation materials selected for high-voltage motors. However, with the popularization of high-voltage motors, the problem of improving the internal heat dissipation efficiency of motors has gradually emerged, which requires the overall thermal conductivity of the corresponding insulation materials to be improved. At present, the thermal conductivity coefficients of conventional pure aramid insulation paper and conventional aramid composite insulation paper are very low, only less than 0.12 W / mK, and the thermal conductivity needs to be improved urgently.

[0004] The thermal conductivity of insulating materials is mainly carried out by phonons. In thermal interface materials, phonons can propagate along the filler lattice, showing excellent thermal conductivity. However, in polymers, the entanglement of molecular chains hinders the propagation of high-speed phonons, so their thermal conductivity is generally poor. Therefore, it is very important to construct a thermal conduction path in the polymer system and reduce the scattering of phonons in the polymer to improve thermal conductivity.

[0005] Chinese patent application CN118563588A discloses a high thermal conductivity aramid composite insulating paper for power equipment, a preparation method and an application thereof, wherein aramid nanofibers with surface modified silver nanoparticles are prepared by mixing aramid nanofibers and silver nitrate; the fibers are then mixed with boron nitride nanosheets and pulped to obtain a composite slurry; finally, the composite slurry is subjected to vacuum filtration to form a film and hot pressing to obtain a composite insulating paper. This technical solution only improves the thermal conductivity of the insulating paper by adding silver nitrate and boron nitride nanosheets to the aramid nanofibers, but the insulating performance of the insulating paper is not very high. It is difficult to achieve insulation, thermal conductivity and mechanical properties while maintaining high performance in current insulating papers. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a high thermal conductivity flexible composite insulating paper and a preparation method and application thereof, wherein the composite insulating paper has excellent thermal conductivity, insulation performance and mechanical properties.

[0007] The technical solution of the present invention to solve the above technical problems is as follows: a highly thermally conductive flexible composite insulating paper, the composite insulating paper comprising at least two layers of aramid insulating paper and a layer of PI film, the aramid insulating paper is pressed on both sides of the PI film respectively, and the PI film and the aramid insulating paper are bonded by a thermally conductive adhesive;

[0008] The aramid insulation paper contains thermal conductive filler, and the PI film is a PI film that has been corona treated.

[0009] Further, the thermally conductive adhesive comprises a mixed thermally conductive filler and a base adhesive, and the mixed thermally conductive filler comprises hydroxylated hexagonal boron nitride nanosheets and nano-alumina powder;

[0010] The sheet diameter of the hydroxylated hexagonal boron nitride (h-BN-OH) nanosheet is 0.1-0.4 μm, the particle size of the nano-alumina powder is 10-200 nm, and the base adhesive is any one of an organic silicone adhesive, a polyurethane adhesive, and an acrylate adhesive;

[0011] The mass ratio of the hydroxylated hexagonal boron nitride nanosheets to the nano-alumina powder is (2-4):1; the amount of the mixed thermal conductive filler is 15-30wt% of the mass of the base adhesive.

[0012] Furthermore, the organic silicone adhesive is BERGQUIST GAP PAD TGP A2600;

[0013] The polyurethane adhesive is selected from any one of LH-101F, LH-1701A, and LOCTITE LA 3640 / LA 6800;

[0014] The acrylic adhesive is DP8425NS.

[0015] Furthermore, the mass content of the thermal conductive filler in the aramid insulation paper is 1-15wt%; the thickness of the PI film is 25-90 μm, the coating thickness of the thermal conductive adhesive is 8-25 μm, and the coating amount of the thermal conductive adhesive is 5-30 g / m 2 .

[0016] Furthermore, the thickness of the composite insulating paper is 80-310 μm, and the basis weight of the composite insulating paper is 140-330 g / m 2 The in-plane thermal conductivity of the aramid insulation paper is ≥0.8 W / (m·K).

[0017] The present invention also discloses a method for preparing a high thermal conductivity flexible composite insulating paper, the preparation method comprising:

[0018] S1. Preparation of aramid insulation paper layer, processing of PI film and preparation of thermal conductive adhesive:

[0019] Preparation of aramid insulation paper layer: h-BN nanosheets are dispersed in a mixed solution of isopropanol and deionized water, and ultrasonically peeled to obtain a hydroxylated hexagonal boron nitride nanosheet dispersion; the desanded meta-aramid chopped fibers are added to the dispersion, and after fully dispersed, meta-aramid precipitated fibers are added, and the mixture is fully decomposed and dispersed again to obtain a mixed slurry of thermal conductive filler and aramid pulp; and the mixture is wet-coated, pressed, dried, and hot-pressed to obtain aramid insulation paper containing thermal conductive filler;

[0020] Treatment of PI film: corona treatment is performed on both sides of the PI film, and the corona-treated PI film is obtained by cleaning and drying;

[0021] Preparation of thermally conductive adhesive: drying a hydroxylated hexagonal boron nitride nanosheet dispersion to obtain hydroxylated hexagonal boron nitride nanosheets, mixing hydroxylated hexagonal boron nitride (h-BN-OH) nanosheets with alumina nanopowder to obtain a mixed thermally conductive filler, slowly adding the mixed thermally conductive filler to the base adhesive during stirring, and mixing evenly to obtain the thermally conductive adhesive;

[0022] S2. Gluing:

[0023] The thermal conductive adhesive obtained in step S1 is uniformly coated on both sides of the corona treated PI film, and a pre-curing treatment is performed to ensure that the adhesive surface maintains adhesion;

[0024] S3. Preparation of composite insulating paper:

[0025] The aramid insulation paper of step S1 is compounded on both sides of the PI film after the pre-curing treatment in step S2, and the composite insulation paper is obtained through pressing and curing.

[0026] Furthermore, the thickness of the PI film is 25-90 μm, the AC voltage of the corona treatment is 10-20 KV; the surface tension value of the PI film after the corona treatment is ≥48 dynes;

[0027] Furthermore, the diameter of the h-BN nanosheet is 0.1-0.4 μm, and the mass ratio of the h-BN nanosheet, isopropanol, and water is (1-15): 393: 500;

[0028] The mass content of the thermal conductive filler in the aramid insulation paper is 1-15wt%;

[0029] The addition amount of the mixed thermal conductive filler in the thermal conductive adhesive is 15-30 wt %, and the mass ratio of hydroxylated hexagonal boron nitride nanosheets to aluminum oxide nanopowder in the thermal conductive adhesive is (2-4):1.

[0030] Furthermore, in step S1, when preparing aramid insulation paper, the hot pressing temperature is 160-260°C, and the hot pressing roller pressure is 30-50 kN / cm 2 ;

[0031] In step S4, the pressing temperature is 60-130°C, and the pressing pressure is 5-15 kN / cm 2 ;

[0032] In step S4, the aging temperature is 40-120°C.

[0033] Preferably, in step S1, when preparing aramid insulation paper, the hot pressing temperature is 180-220°C, and the rolling pressure is 35-45 kN / cm 2 ;

[0034] In step S4, the pressing temperature is 75-105°C, and the pressing pressure is 8-12 kN / cm 2 ;

[0035] In step S4, the aging temperature is 50-65°C.

[0036] The invention also discloses an application of a high thermal conductivity flexible composite insulating paper, wherein the composite insulating paper is applied in the field of electrical equipment insulation.

[0037] The beneficial effects of the present invention are:

[0038] The composite insulating paper of the present invention evenly embeds the thermal conductive filler inside the aramid paper, and by compounding with the thermal conductive adhesive and the thermal conductive PI film, a thermal conductive path is constructed at the interface to solve the problem of difficult heat transfer at the interface. While ensuring the insulation performance of the composite paper, the thermal conductivity is greatly improved. Compared with the pure aramid paper of the same specification, the thermal conductivity of the composite insulating paper can even be improved by 13 times. The composite insulating paper also has excellent thermal conductivity, insulation performance and mechanical properties. In addition, compared with the thermal conductive aramid insulating pure paper of the same specification, the composite insulating paper prepared by the present invention has a lower manufacturing cost.

[0039] The present invention introduces an insulating PI film coated with a thermally conductive adhesive into the composite insulating paper. On the one hand, the presence of the thermally conductive adhesive not only plays a bonding role, but also can solve the problem of poor heat transfer performance at the interface. On the other hand, the PI film itself has excellent insulating and mechanical properties. After being composited with the aramid insulating paper by the thermally conductive adhesive, the dielectric strength and elongation at break are significantly improved compared with pure aramid insulating paper of the same specification.

[0040] The present invention introduces a PI film into the composite insulating paper. Compared with thermally conductive aramid insulating paper of the same specification, the introduction of the PI film can effectively reduce the manufacturing cost of the insulating paper, and the preparation method is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The present invention is a process flow chart for preparing the composite insulating paper. DETAILED DESCRIPTION

[0042] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0044] A highly thermally conductive flexible composite insulating paper, the composite insulating paper comprising at least two layers of aramid insulating paper and a layer of PI film, the aramid insulating paper being pressed onto both sides of the PI film, and the PI film and the aramid insulating paper being bonded by a thermally conductive adhesive;

[0045] The aramid insulation paper contains thermal conductive filler, and the PI film is a PI film that has been corona treated.

[0046] Specifically, the thermally conductive adhesive comprises a mixed thermally conductive filler and a base adhesive, and the mixed thermally conductive filler comprises hydroxylated hexagonal boron nitride nanosheets and nano-alumina powder;

[0047] The sheet diameter of the hydroxylated hexagonal boron nitride nanosheets is 0.1-0.4 μm, the particle size of the nano-alumina powder is 10-200 nm, and the base adhesive is any one of an organic silicone adhesive, a polyurethane adhesive, and an acrylate adhesive;

[0048] The mass ratio of the hydroxylated hexagonal boron nitride nanosheets to the nano-alumina powder is (2-4):1; the amount of the mixed thermal conductive filler is 15-30wt% of the mass of the base adhesive.

[0049] Specifically, the organic silicone adhesive is BERGQUIST GAP PAD TGP A2600;

[0050] The polyurethane adhesive is selected from any one of LH-101F, LH-1701A, and LOCTITE LA 3640 / LA 6800;

[0051] The acrylic adhesive is DP8425NS.

[0052] Specifically, the mass content of the thermal conductive filler in the aramid insulation paper is 1-15wt%; the thickness of the PI film is 25-90 μm, the coating thickness of the thermal conductive adhesive is 8-25 μm, and the coating amount of the thermal conductive adhesive is 5-30 g / m 2 .

[0053] Preferably, the PI film has a thickness of 38-75 μm.

[0054] More preferably, under the condition of using the same thermally conductive adhesive, when the coating thickness of the thermally conductive adhesive is 8-25 μm and the mass content of the thermally conductive filler in the aramid insulating paper is 1-15 wt%, assuming that the coating thickness of the thermally conductive adhesive is Y, in μm, and the mass content of the thermally conductive filler in the aramid insulating paper is X, in wt%, then the relationship between the coating thickness of the thermally conductive adhesive and the content of the thermally conductive filler in the aramid insulating paper satisfies Y≥20X -0.34 It is more conducive to obtaining composite insulating paper with excellent comprehensive performance.

[0055] Specifically, the thickness of the composite insulating paper is 80-310 μm, and the basis weight of the composite insulating paper is 140-330 g / m 2 The in-plane thermal conductivity of the aramid insulation paper is ≥0.8 W / (m·K).

[0056] like Figure 1 As shown, a method for preparing a high thermal conductivity flexible composite insulating paper, the preparation method is:

[0057] S1. Preparation of aramid insulation paper layer, processing of PI film and preparation of thermal conductive adhesive:

[0058] Preparation of aramid insulation paper layer: h-BN nanosheets are dispersed in a mixed solution of isopropanol and deionized water, and ultrasonically stripped for 12 hours to obtain a hydroxylated hexagonal boron nitride nanosheet dispersion; the desanded meta-aramid chopped fibers are added to the dispersion, and after being fully dispersed, meta-aramid precipitated fibers are added, and the mixture is fully decomposed and dispersed again to obtain a mixed slurry of thermal conductive filler and aramid pulp; and the mixture is wet-coated, pressed, dried, and hot-pressed to obtain aramid insulation paper containing thermal conductive filler;

[0059] Treatment of PI film: corona treatment is performed on both sides of the PI film, and the corona-treated PI film is obtained by cleaning and drying;

[0060] Preparation of thermally conductive adhesive: h-BN nanosheets are dispersed in a mixed solution of isopropanol and deionized water, and ultrasonically peeled for 12 hours to obtain a hydroxylated hexagonal boron nitride nanosheet dispersion; the hydroxylated hexagonal boron nitride nanosheet dispersion is dried to obtain hydroxylated hexagonal boron nitride nanosheets, and the hydroxylated hexagonal boron nitride (h-BN-OH) nanosheets are mixed with alumina nanopowder to obtain a mixed thermally conductive filler, and the mixed thermally conductive filler is slowly added to the base adhesive during stirring, and the thermally conductive adhesive is obtained after being evenly mixed;

[0061] S2. Gluing:

[0062] The thermal conductive adhesive obtained in step S1 is uniformly coated on both sides of the corona treated PI film, and a pre-curing treatment is performed to ensure that the adhesive surface maintains adhesion;

[0063] S3. Preparation of composite insulating paper:

[0064] The aramid insulation paper of step S1 is compounded on both sides of the PI film pre-cured in step S2, and the compounded materials are pressed by high-temperature pressing rollers and put into a curing room for 5 days to obtain the high thermal conductivity flexible composite insulation paper.

[0065] Specifically, the thickness of the PI film is 25-90 μm, the AC voltage of the corona treatment is 10-20 KV, and the surface tension value of the PI film after the corona treatment is ≥48 dynes.

[0066] More specifically, in the range of PI film thickness of 25~90 μm and corona treatment AC voltage of 10~20 KV, assuming that the PI film thickness is H, in μm; the AC voltage of the corona treatment is U, in KV; then the data relationship between the AC voltage U and the PI film thickness satisfies U=u±2.2, u=7.2ln(H)-14. Through the data relationship of this formula, the staff can adjust the AC voltage of the corona treatment according to the thickness of the PI film, so as to directly obtain a PI film with qualified corona treatment, because if the voltage is too large during the corona treatment, it is easy to cause damage to the PI film, which ultimately affects the insulation performance of the composite insulating paper. If the voltage is too small, it will cause the thermal conductivity of the composite insulating paper to deteriorate. Selecting a suitable voltage according to the PI film thickness is more conducive to obtaining a composite insulating paper with excellent comprehensive performance.

[0067] In an embodiment of the present invention, the diameter of the h-BN nanosheet is 0.1-0.4 μm, the mass content of h-BN-OH in the aramid insulation paper is 1-15wt%, and the mass ratio of the h-BN nanosheet, isopropyl alcohol, and water is (1-15):393:500. During the production process, the usage ratio of meta-aramid chopped fibers and meta-aramid fibrils can be selected according to the performance requirements of the aramid insulation paper. In an embodiment of the present invention, the mass ratio of meta-aramid chopped fibers and meta-aramid fibrils is 1:1.5, and the mass ratio of h-BN nanosheets to meta-aramid chopped fibers and meta-aramid fibrils is (2-30):0.78:1.17.

[0068] Specifically, in the dispersion, the mass concentration of h-BN-OH is 0.1-1.7 wt %.

[0069] More specifically, in an embodiment of the present invention, the meta-aramid chopped fibers are Tametar meta-aramid chopped fibers, having a fineness of 1.5-5D and a fiber length of 5-10 mm, and the meta-aramid fibrils are Tametar meta-aramid fibrils.

[0070] More specifically, in the embodiment of the present invention, in step S2, the thermal conductive adhesive is applied by wire rod scraping, and the amount of adhesive applied is 5-30 g / m 2 .

[0071] Preferably, the coating thickness of the thermally conductive adhesive is 8-25 μm.

[0072] Specifically, in step S1, the mass concentration of the h-BN nanosheets in the mixed solution is 0.1-1.5 wt %.

[0073] Specifically, in step S1, when preparing aramid insulation paper, the hot pressing temperature is 160-260°C, and the hot pressing roller pressure is 30-50 kN / cm 2 ;

[0074] In step S4, the pressing temperature is 60-130°C, and the pressing pressure is 5-15 kN / cm 2 ;

[0075] In step S4, the aging temperature is 40-120°C.

[0076] Preferably, in step S1, when preparing aramid insulation paper, the hot pressing temperature is 180-220°C, and the rolling pressure is 35-45 kN / cm 2 ;

[0077] In step S4, the pressing temperature is 75-105°C, and the pressing pressure is 8-12 kN / cm 2 ;

[0078] In step S4, the aging temperature is 50-65°C.

[0079] Example 1

[0080] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0081] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0082] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0083] S2. Preparation of thermal conductive adhesive:

[0084] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder (10-200 nm), and slowly added to 50 g of LBERGQUISTGAP PAD TGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0085] S3, Gluing:

[0086] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0087] S4. Preparation of composite insulating paper:

[0088] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0089] Example 2

[0090] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0091] 2 g of h-BN nanosheets (sheet diameter of 0.1-0.4 μm) were weighed and dissolved in a mixed solution of isopropanol and deionized water (786 g of isopropanol and 1000 g of deionized water), and ultrasonic peeling was performed for 12 h to obtain a h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78 g) and meta-aramid fiber precipitation (1.17 g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220 ° C and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers is obtained, and the mass content of h-BN-OH in the aramid insulation paper is 1wt%.

[0092] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0093] S2. Preparation of thermal conductive adhesive:

[0094] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added into 50 g of BERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0095] S3, Gluing:

[0096] The thermal conductive adhesive obtained from S2 is evenly coated on both sides of the dried PI film with a thickness of 10 μm, and the PI film after adhesive application is placed at room temperature for 1 day for colloid pre-curing.

[0097] S4. Preparation of composite insulating paper:

[0098] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0099] Example 3

[0100] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0101] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic exfoliation was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0102] A PI film with a thickness of 90 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0103] S2. Preparation of thermal conductive adhesive:

[0104] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added into 50 g of BERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0105] S3, Gluing:

[0106] The thermal conductive adhesive obtained from S2 is evenly coated on both sides of the dried PI film with a thickness of 10 μm, and the PI film after adhesive application is placed at room temperature for 1 day for colloid pre-curing.

[0107] S4. Preparation of composite insulating paper:

[0108] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0109] Example 4

[0110] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0111] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0112] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0113] S2. Preparation of thermal conductive adhesive:

[0114] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 11.25 g of h-BN-OH nanosheets were mixed with 3.75 g of alumina nanopowder, and slowly added into 50 g of LOCTITE LA 3640_LA 6800 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0115] S3, Gluing:

[0116] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0117] S4. Preparation of composite insulating paper:

[0118] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0119] Example 5

[0120] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0121] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic exfoliation was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0122] A PI film with a thickness of 75 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0123] S2. Preparation of thermal conductive adhesive:

[0124] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LH-101F adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0125] S3, Gluing:

[0126] The thermal conductive adhesive obtained from S2 was evenly coated on both sides of the dried PI film with a thickness of 25 μm, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0127] S4. Preparation of composite insulating paper:

[0128] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0129] Example 6

[0130] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0131] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic exfoliation was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 160℃ and 30 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0132] A PI film with a thickness of 38 μm was subjected to corona treatment at a voltage of 10 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0133] S2. Preparation of thermal conductive adhesive:

[0134] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 5.0 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and the mixture was slowly added to 50 g of BERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0135] S3, Gluing:

[0136] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0137] S4. Preparation of composite insulating paper:

[0138] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0139] Example 7

[0140] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0141] 30 g h-BN nanosheets (sheet diameter 0.1-0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786 g isopropanol and 1000 g deionized water), and ultrasonic exfoliation was performed for 12 h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78 g) and meta-aramid fiber precipitation (1.17 g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220 ° C and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 15wt%.

[0142] A PI film with a thickness of 25 μm was subjected to corona treatment at a voltage of 10 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0143] S2. Preparation of thermal conductive adhesive:

[0144] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 8.0 g of h-BN-OH nanosheets were mixed with 2.0 g of alumina nanopowder, and slowly added to 50 g of LH-1701A adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0145] S3, Gluing:

[0146] The thermal conductive adhesive obtained from S2 with a thickness of 8 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0147] S4. Preparation of composite insulating paper:

[0148] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 60°C and a roller pressure of 5 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper is placed in a 40° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0149] Example 8

[0150] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0151] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fibrils (1.17g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 260℃ and 50 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0152] A PI film with a thickness of 90 μm was subjected to corona treatment at a voltage of 20 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0153] S2. Preparation of thermal conductive adhesive:

[0154] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of DP8425NS adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0155] S3, Gluing:

[0156] The thermal conductive adhesive obtained by S2 with a thickness of 12 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0157] S4. Preparation of composite insulating paper:

[0158] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 105°C and a roller pressure of 15 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 65° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0159] Example 9

[0160] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0161] 14 g h-BN nanosheets (sheet diameter 0.1-0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786 g isopropanol and 1000 g deionized water), and ultrasonic peeling was performed for 12 h to obtain h-BN-OH nanosheet dispersion. Meta-aramid chopped fibers (0.78 g) and meta-aramid fibrils (1.17 g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220 ° C and 35 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 7wt%.

[0162] A PI film with a thickness of 75 μm was subjected to corona treatment at a voltage of 17 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0163] S2. Preparation of thermal conductive adhesive:

[0164] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added into 50 g of BERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0165] S2. Gluing:

[0166] The thermal conductive adhesive obtained by S2 with a thickness of 12 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0167] S3. Preparation of composite insulating paper:

[0168] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S2, and pressed by a high-temperature roller at 130°C with a roller pressure of 5 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper is placed in a 120° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0169] Example 10

[0170] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0171] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0172] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0173] S2. Preparation of thermal conductive adhesive:

[0174] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added into 50 g of BERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0175] S2. Gluing:

[0176] The thermal conductive adhesive obtained from S2 with a thickness of 8 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0177] S3. Preparation of composite insulating paper:

[0178] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S2, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0179] Embodiment 11

[0180] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0181] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic exfoliation was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0182] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 10 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0183] S2. Preparation of thermal conductive adhesive:

[0184] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added into 50 g of BERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0185] S2. Gluing:

[0186] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0187] S3. Preparation of composite insulating paper:

[0188] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S2, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0189] Example 12

[0190] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0191] 18 g h-BN nanosheets (sheet diameter 0.1-0.4 μm) were weighed and dissolved in a mixed solution of 2000 g isopropanol and deionized water (786 g isopropanol and 1000 g deionized water), and ultrasonic peeling was performed for 12 h to obtain h-BN-OH nanosheet dispersion. Meta-aramid chopped fibers (0.78 g) and meta-aramid fiber precipitation (1.17 g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220 ° C and 50 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0192] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 20 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0193] S2. Preparation of thermal conductive adhesive:

[0194] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added into 50 g of BERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0195] S2. Gluing:

[0196] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0197] S3. Preparation of composite insulating paper:

[0198] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S2, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0199] Comparative Example 1

[0200] The same method as in Example 1 is used, except that the amount of h-BN nanosheets used is higher than the range specified in the present invention. The specific operation process is as follows:

[0201] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0202] 36 g h-BN nanosheets (sheet diameter 0.1-0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786 g isopropanol and 1000 g deionized water), and ultrasonic exfoliation was performed for 12 h to obtain h-BN-OH nanosheet dispersion. Meta-aramid chopped fibers (0.78 g) and meta-aramid fibrils (1.17 g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220 ° C and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 18wt%.

[0203] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0204] S2. Preparation of thermal conductive adhesive:

[0205] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0206] S3, Gluing:

[0207] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0208] S4. Preparation of composite insulating paper:

[0209] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0210] Comparative Example 2

[0211] The same method as in Example 1 is used, except that the thickness of the selected PI film is higher than the thickness range specified in the present invention. The specific operation process is as follows:

[0212] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0213] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic exfoliation was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0214] A PI film with a thickness of 100 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0215] S2. Preparation of thermal conductive adhesive:

[0216] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0217] S3, Gluing:

[0218] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0219] S4. Preparation of composite insulating paper:

[0220] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0221] Comparative Example 3

[0222] The same method as in Example 1 is used, except that the coating thickness of the conductive adhesive is higher than the range specified in the present invention. The specific operation process is as follows:

[0223] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0224] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic exfoliation was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0225] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0226] S2. Preparation of thermal conductive adhesive:

[0227] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0228] S3, Gluing:

[0229] The thermal conductive adhesive obtained from S2 with a thickness of 35 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0230] S4. Preparation of composite insulating paper:

[0231] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0232] Comparative Example 4

[0233] The same method as in Example 1 is used, except that in step S1, the hot pressing temperature of the wet-coated aramid paper is higher than the range specified in the present invention. The specific operation process is as follows:

[0234] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0235] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fibrils (1.17g) were added to the above dispersion in sequence, and a pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 280℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0236] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0237] S2. Preparation of thermal conductive adhesive:

[0238] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0239] S3, Gluing:

[0240] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0241] S4. Preparation of composite insulating paper:

[0242] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0243] Comparative Example 5

[0244] The same method as in Example 1 is used, except that in step S1, the hot pressing pressure of the wet-made aramid paper is higher than the range specified in the present invention. The specific operation process is as follows:

[0245] The same method as in Example 1 is used, except that in step S1, the hot pressing temperature of the wet-coated aramid paper is higher than the range specified in the present invention. The specific operation process is as follows:

[0246] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0247] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient disintegration and dispersion. The pulp mixture was squeezed and dried at 220℃ and 60 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0248] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0249] S2. Preparation of thermal conductive adhesive:

[0250] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0251] S3, Gluing:

[0252] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0253] S4. Preparation of composite insulating paper:

[0254] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0255] Comparative Example 6

[0256] The same method as in Example 1 is used, except that the pressing temperature in step S4 is higher than the temperature range specified in the present invention. The specific operation process is as follows:

[0257] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0258] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0259] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0260] S2. Preparation of thermal conductive adhesive:

[0261] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0262] S3, Gluing:

[0263] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0264] S4. Preparation of composite insulating paper:

[0265] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 150°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0266] Comparative Example 7

[0267] The same method as in Example 1 is used, except that the pressing pressure in step S4 is higher than the temperature range specified in the present invention. The specific operation process is as follows:

[0268] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0269] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0270] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0271] S2. Preparation of thermal conductive adhesive:

[0272] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0273] S3, Gluing:

[0274] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0275] S4. Preparation of composite insulating paper:

[0276] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 20 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0277] Comparative Example 8

[0278] The same method as in Example 1 is used, except that the aging temperature in step S3 is higher than the temperature range specified in the present invention. The specific operation process is as follows:

[0279] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0280] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0281] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0282] S2. Preparation of thermal conductive adhesive:

[0283] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0284] S3, Gluing:

[0285] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0286] S4. Preparation of composite insulating paper:

[0287] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper is placed in a 130° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0288] Comparative Example 9

[0289] The same method as in Example 1 is adopted, except that the corona treatment voltage in step S1 is higher than the range specified in the present invention. The specific operation process is as follows:

[0290] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0291] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0292] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 22 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0293] S2. Preparation of thermal conductive adhesive:

[0294] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 7.5 g of h-BN-OH nanosheets were mixed with 2.5 g of alumina nanopowder, and slowly added to 50 g of LBERGQUIST GAP PADTGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0295] S3, Gluing:

[0296] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0297] S4. Preparation of composite insulating paper:

[0298] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0299] Comparative Example 10

[0300] The same method as in Example 1 is used, except that the amount of thermally conductive filler in the adhesive in step S2 is higher than the range specified in the present invention. The specific operation process is as follows:

[0301] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0302] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0303] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0304] S2. Preparation of thermal conductive adhesive:

[0305] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 15 g of h-BN-OH nanosheets were mixed with 5 g of alumina nanopowder, and the mixture was slowly added to 50 g of LBERGQUIST GAP PAD TGPA2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0306] S3, Gluing:

[0307] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0308] S4. Preparation of composite insulating paper:

[0309] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0310] Comparative Example 11

[0311] The same method as in Example 1 is used, except that no nano-alumina powder is added to the adhesive in step S2. The specific operation process is as follows:

[0312] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0313] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0314] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0315] S2. Preparation of thermal conductive adhesive:

[0316] The h-BN-OH nanosheet dispersion obtained in S1 was dried to obtain h-BN-OH nanosheets, 10 g of h-BN-OH nanosheets were slowly added to 50 g of LBERGQUIST GAP PAD TGP A2600 adhesive during stirring, and mechanical stirring was continued for 2 hours to obtain a thermally conductive adhesive;

[0317] S3, Gluing:

[0318] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0319] S4. Preparation of composite insulating paper:

[0320] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0321] Comparative Example 12

[0322] The same method as in Example 1 is used, except that no h-BN-OH nanosheets are added to the adhesive in step S2. The specific operation process is as follows:

[0323] S1. Preparation of aramid insulation paper layer and treatment of PI film:

[0324] 18g h-BN nanosheets (sheet diameter 0.1~0.4 μm) were weighed and dispersed in a mixed solution of isopropanol and deionized water (786g isopropanol and 1000g deionized water), and ultrasonic peeling was performed for 12h to obtain h-BN-OH nanosheet dispersion. Meta-aramid short fibers (0.78g) and meta-aramid fiber precipitation (1.17g) were added to the above dispersion in sequence, and the pulp mixture was obtained after sufficient dispersibility and dispersion. The pulp mixture was squeezed and dried at 220℃ and 40 kN / cm 2 After hot pressing, aramid insulation paper uniformly embedded with thermal conductive fillers was obtained, and the mass content of h-BN-OH in the aramid insulation paper was 9wt%.

[0325] A PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried to obtain a PI film after corona treatment.

[0326] S2. Preparation of thermal conductive adhesive:

[0327] Take 10 g of aluminum oxide nanopowder, slowly add it to 50 g of LBERGQUIST GAP PAD TGPA2600 adhesive during stirring, and continue mechanical stirring for 2 hours to obtain a thermally conductive adhesive;

[0328] S3, Gluing:

[0329] The thermal conductive adhesive obtained by S2 with a thickness of 10 μm was uniformly coated on both sides of the corona-treated PI film, and the PI film after adhesive application was placed at room temperature for 1 day for colloid pre-curing.

[0330] S4. Preparation of composite insulating paper:

[0331] The aramid insulating paper of step S1 is laminated on both sides of the PI film pre-cured in step S3, and pressed by a high-temperature roller at 90°C with a roller pressure of 8 kN / cm 2 Finally, the double-sided composite thermally conductive insulating paper was placed in a 60° C. curing room for 5 days to obtain a highly thermally conductive multi-layer flexible composite insulating paper.

[0332] Comparative Example 13

[0333] This comparative example adopts a conventional insulating composite paper preparation method, and the selected composite materials are all non-thermal conductive modified materials. The specific operation process is as follows:

[0334] Weigh 0.78 g of meta-aramid chopped fibers and 1.17 g of meta-aramid fibrids and add them into deionized water. After being fully dispersed, a pulp mixture is obtained. The pulp mixture is squeezed and dried at 220°C and 40 kN / cm 2 After hot pressing, aramid paper is obtained.

[0335] A non-thermal conductive PI film with a thickness of 50 μm was subjected to corona treatment at a voltage of 15 KV. The treated film surface was dusted, cleaned with ethanol and dried. A 35 μm thick LBERGQUIST GAPPAD TGP A2600 adhesive before modification was evenly coated on both sides of the dried PI film. The PI film after adhesive application was pre-cured according to the adhesive curing conditions.

[0336] The aramid paper prepared above was bonded to the two sides of the pre-cured adhesive surface, and pressed with a high-temperature pressure roller at 80°C and a roller pressure of 8 kN / cm 2 Finally, the composite flexible insulating paper was placed in a 60° C. curing room for 5 days to obtain a conventional multi-layer flexible composite insulating paper.

[0337] The insulating composite paper samples of the above embodiments and comparative examples were subjected to performance tests. The specific data results are shown in Table 1 below. The measurement methods involved refer to GB / T5591.2-2017 and GB / T 29313-2012. The appearance inspection after composite mainly includes the evaluation of softness and paper surface flatness.

[0338] Table 1 Material properties

[0339]

[0340] It can be seen from the data in Table 1 that the composite insulating paper prepared by the preparation method of the present invention in Examples 1-12 has excellent thermal conductivity, insulation and mechanical comprehensive properties. Moreover, it can be seen from the data comparison between Example 1 and Example 10 that when the thickness of the thermal conductive adhesive and the content of the thermal conductive filler cooperate with each other, it is more conducive to obtaining a composite insulating paper with better comprehensive performance. It can be seen from the data comparison between Example 1 and Examples 11-12 that when the thickness of the PI film and the voltage of the corona treatment cooperate with each other, it is more conducive to obtaining a composite insulating paper with excellent comprehensive performance.

[0341] In addition, it can be seen from the comparative data in Table 1 that when the mass concentration of h-BN in the dispersion is 0.9wt% (Example 1), the plane thermal conductivity of the prepared composite insulating paper is 0.815 W / mK, which is equivalent to 7.3 times the thermal conductivity of the conventional composite insulating paper in the comparative example 11, which significantly improves the thermal conductivity of the composite insulating paper. In addition, while improving the thermal conductivity of the composite insulating paper, the thermally conductive modified composite insulating paper prepared by the present invention still retains higher mechanical properties and insulation properties relative to the conventional composite insulating paper in the comparative example 11. When the mass concentration of h-BN in the dispersion is 0.9wt%, the longitudinal tensile strength of the prepared composite insulating paper is 155.32 N / cm, the elongation at break is 10.56%, and the dielectric strength is 64.21 KV / mm. The retention rates of tensile strength, elongation at break, and dielectric strength of the conventional composite insulating paper before thermal conductive modification are 88.14%, 70.07%, and 77.86%, respectively.

[0342] From the data comparison between Example 1 and Comparative Example 1, it can be seen that there is an optimal concentration range for the doping amount of h-BN-OH in aramid paper. When a certain doping amount is exceeded, the mechanical properties and insulation properties of the aramid paper are significantly reduced, which leads to a decrease in the comprehensive performance of the insulating paper after compounding.

[0343] From the data comparison of Example 1 and Comparative Example 2, it can be seen that increasing the thickness of the PI film used in the preparation of the composite insulating paper will improve the mechanical properties and insulating properties of the composite paper, but the thermal conductivity will decrease significantly, and the excessively high film thickness will make the composite insulating paper as a whole harder, which is not conducive to the subsequent use of the insulating paper.

[0344] From the data comparison between Example 1 and Comparative Example 3, it can be seen that the increase in the thickness of the adhesive coating will not only reduce the insulation performance, but also make the material as a whole harder.

[0345] From the data comparison of Example 1 and Comparative Example 4, it can be seen that after wet-processing of aramid paper, if the hot pressing temperature is too high, the aramid paper will become partially brittle, and the aramid paper prepared in this way cannot be used for the subsequent preparation of composite paper.

[0346] From the data comparison of Example 1 and Comparative Example 5, it can be seen that after wet-processing of aramid paper, if the pressure of the pressing roller is too high during hot pressing, obvious wrinkles will appear on the surface of the aramid paper, and such aramid paper cannot be used in the preparation of composite paper.

[0347] From the data comparison of Example 1 and Comparative Example 6, it can be seen that after the aramid paper is bonded to the adhesive surface, if the hot pressing temperature is too high, the composite paper will be glued and the fluidity of the adhesive will increase. Under the action of the pressing roller, it will flow out from the edge of the composite paper and stick to the surface of the pressing roller, causing equipment pollution.

[0348] From the comparison of the data of Example 1 and Comparative Example 7, it can be seen that after the aramid paper is bonded to the adhesive surface, if the bonding pressure is too large, it will cause obvious local wrinkles on the composite insulating paper, which does not meet the requirement of a smooth surface of the composite insulating paper.

[0349] From the data comparison of Example 1 and Comparative Example 8, it can be seen that the composite thermally conductive modified insulating paper needs to be placed in a curing room for curing to ensure that the adhesive is completely cured, but the curing temperature should not be too high, otherwise debonding and glue flow will occur before the adhesive is completely cured, making the appearance and performance of the composite insulating paper fail to meet the requirements.

[0350] From the comparison of the data of Example 1 and Comparative Example 9, it can be seen that when the PI film is corona treated, the corona voltage should not be too high, otherwise it will affect the secondary bond force between the film molecules and cause brittleness, resulting in a significant loss of its mechanical properties.

[0351] From the data comparison between Example 1 and Comparative Example 10, it can be seen that an excessive content of thermally conductive filler in the adhesive will directly affect the bonding performance of the adhesive and have an adverse effect on the subsequent compounding steps.

[0352] From the data comparison of Example 1 and Comparative Examples 11-12, it can be seen that if nano-alumina powder is not added to the adhesive, the thermal conductivity of the composite paper will be poor; if h-BN-OH is not added, the composite paper will be hard and the thermal conductivity will be poor, because the combination of nano-alumina powder and h-BN-OH added to the adhesive is more conducive to obtaining composite insulating paper with excellent comprehensive performance. This is because the two-dimensional h-BN-OH nanosheet is the main structure of the thermal conductivity path, and the small-sized nano-alumina powder can connect adjacent nanosheets to further form a thermal conductivity network with more connection points. This structure of the thermal conductivity network has a more effective thermal conductivity effect than the thermal conductivity path constructed by a single component filler.

[0353] In addition, nano-alumina powder has strong rigidity, and large amounts of doping will affect the flexibility of the adhesive, making the composite insulating paper overall harder, which is not conducive to subsequent use.

[0354] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0355] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a high thermal conductivity flexible composite insulating paper, characterized in that: The composite insulating paper comprises at least two layers of aramid insulating paper and a layer of PI film, the aramid insulating paper is pressed on both sides of the PI film respectively, and the PI film and the aramid insulating paper are bonded by a thermally conductive adhesive; the preparation method is: S1. Preparation of aramid insulation paper layer, processing of PI film and preparation of thermal conductive adhesive: Preparation of aramid insulation paper layer: h-BN nanosheets are dispersed in a mixed solution of isopropanol and deionized water, and ultrasonically peeled to obtain a hydroxylated hexagonal boron nitride nanosheet dispersion; the desanded meta-aramid chopped fibers are added to the dispersion, and after sufficient dispersion, meta-aramid precipitated fibers are added, and the mixture is fully decomposed and dispersed again to obtain a mixed slurry of thermal conductive filler and aramid pulp; after wet papermaking, pressing, drying, and hot pressing, aramid insulation paper containing thermal conductive filler is obtained; when preparing aramid insulation paper, the hot pressing temperature is 160~260℃, and the hot pressing roller pressure is 30~50 kN / cm 2 ; Treatment of PI film: corona treatment is performed on both sides of the PI film, and the corona-treated PI film is obtained after cleaning and drying; the AC voltage of the corona treatment is 10~20 KV; Preparation of thermally conductive adhesive: drying a hydroxylated hexagonal boron nitride nanosheet dispersion to obtain hydroxylated hexagonal boron nitride nanosheets, mixing the hydroxylated hexagonal boron nitride nanosheets with alumina nanopowder to obtain a mixed thermally conductive filler, slowly adding the mixed thermally conductive filler to the base adhesive during stirring, and mixing evenly to obtain the thermally conductive adhesive; S2. Gluing: The thermal conductive adhesive obtained in step S1 is uniformly coated on both sides of the corona treated PI film, and a pre-curing treatment is performed to ensure that the adhesive surface maintains adhesion; S3. Preparation of composite insulating paper: The aramid insulation paper of step S1 is laminated on both sides of the PI film pre-cured in step S2, and the composite insulation paper is obtained by lamination and aging; the lamination temperature is 60-130°C, and the lamination pressure is 5-15 kN / cm 2 ; The aging temperature is 40~120℃; The diameter of the h-BN nanosheet is 0.1-0.4 μm, and the mass ratio of the h-BN nanosheet, isopropanol, and water is (1-15): 393:500; The mass content of the thermal conductive filler in the aramid insulation paper is 1-15wt%; The amount of the mixed thermal conductive filler added to the thermal conductive adhesive is 15-30 wt %, the mass ratio of the hydroxylated hexagonal boron nitride nanosheets to the alumina nanopowder in the thermal conductive adhesive is (2-4):1, and the particle size of the nano alumina powder is 10-200 nm; The thickness of the PI film is 25-90 μm, the coating thickness of the thermal conductive adhesive is 8-25 μm, and the coating amount of the thermal conductive adhesive is 5-30 g / m 2 .

2. The method for preparing a high thermal conductivity flexible composite insulating paper according to claim 1, characterized in that: The basic adhesive is any one of organic silicone adhesive, polyurethane adhesive and acrylic adhesive.

3. The method for preparing a high thermal conductivity flexible composite insulating paper according to claim 2, characterized in that: The organic silicone adhesive is BERGQUIST GAP PAD TGP A2600; The polyurethane adhesive is selected from any one of LH-101F, LH-1701A, and LOCTITE LA 3640 / LA 6800; The acrylic adhesive is DP8425NS.

4. The method for preparing a high thermal conductivity flexible composite insulating paper according to claim 1, characterized in that: The thickness of the composite insulating paper is 80-310 μm, and the basis weight of the composite insulating paper is 140-330 g / m 2 .

5. The method for preparing a high thermal conductivity flexible composite insulating paper according to claim 1, characterized in that: The surface tension of the PI film after corona treatment is ≥48 dynes.

6. An application of the high thermal conductivity flexible composite insulation paper prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The composite insulating paper is used in the field of electrical equipment insulation.

Citation Information

Patent Citations

  • High-thermal-conductivity aramid fiber composite insulation paper for electrical equipment, preparation method and application of high-thermal-conductivity aramid fiber composite insulation paper

    CN118563588A

  • High thermal conduction film reinforcement mica tape, preparation method thereof and application

    CN106626626A

  • H-class flexible composite insulation material

    CN107393664A

  • Heat conduction type aramid nano insulation paper and preparation method thereof

    CN108978328A